1989
DOI: 10.1161/01.res.65.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Direct actions of cocaine on cardiac cellular electrical activity.

Abstract: The hypothesis that cocaine has Class I-type antiarrhythmic drug effects was tested in tissues isolated from rabbit heart with standard microelectrode methods. Propranolol (1 microM) was used to block beta-adrenergic effects. The actions of cocaine on cellular electrophysiology were concentration- and time-dependent and were reversible. In paced right atrial (RA) and right ventricular papillary (RVP) tissues, cocaine produced a profound prolongation of the effective refractory period (ERP) assessed by either p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 14 publications
(6 reference statements)
4
43
0
Order By: Relevance
“…On the ECG, this is manifested by a prolongation of the PR, QRS, and QT intervals35; cocaine also prolongs the refractoriness of atrial and ventricular muscle. 36 In this sense, the drug's electrophysiological properties are similar to other type I antiarrhythmic agents such as procainamide and quinidine. This direct local anesthetic or membrane-stabilizing property may be responsible for a negative inotropic effect of cocaine.…”
Section: U Clinical Progress Seriesmentioning
confidence: 97%
“…On the ECG, this is manifested by a prolongation of the PR, QRS, and QT intervals35; cocaine also prolongs the refractoriness of atrial and ventricular muscle. 36 In this sense, the drug's electrophysiological properties are similar to other type I antiarrhythmic agents such as procainamide and quinidine. This direct local anesthetic or membrane-stabilizing property may be responsible for a negative inotropic effect of cocaine.…”
Section: U Clinical Progress Seriesmentioning
confidence: 97%
“…The drug has class I-type activity, with significant effects on myocardial refractoriness. 40 In addition, cocaine can have a proarrhythmic effect similar to that induced by quinidine as the result of triggered activity from early afterdepolarizations associated with a prolonged QT interval. Thus, cocaine ingestion could induce ventricular arrhythmia independent of its effects on coronary arteries 41 and in the absence of toxic levels.…”
Section: Possible Causes Of Scd In Patients With Structurally Normal mentioning
confidence: 99%
“…Such conduction disturbances could contribute to the generation of reentrant arrhythmias, and previous investigators have emphasized this concept of cocaine arrhythmogenesis"~- 15; however, it has also been shown that cocaine prolongs repolarization. 15 In this respect, the effects of cocaine are similar to those of class IA antiarrhythmic drugs, that is, Na+ channel block and prolongation of repolarization. Class IA antiarrhythmic drugs, especially quinidine, have been shown to induce triggered activity arising from early afterdepolarizations (EADs), '8 19 which have been proposed as a potential mechanism of arrhythmias in patients with acquired long QT syndrome.…”
mentioning
confidence: 96%
“…However, it has also been proposed that cocaine-related deaths of cardiac origin may occur in the absence of myocardial infarction, presumably because of direct adverse effects on cardiac electrophysiology. [11][12][13][14][15] Cocaine is a local anesthetic, and its blockade of Na+ channels1617 may produce conduction disturbances in the heart. Such conduction disturbances could contribute to the generation of reentrant arrhythmias, and previous investigators have emphasized this concept of cocaine arrhythmogenesis"~- 15; however, it has also been shown that cocaine prolongs repolarization.…”
mentioning
confidence: 99%